Pemanfaatan Sistem Informasi Desa untuk Peningkatan Kapasitas Aparatur Desa - Diana Hertati; Nurhadi Nurhadi; Indira Arundirasari (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
A web-based village government information system can encourage the community to participate in village development actively. On the other hand, web-based information transparency can improve the orderly administration of village government. The main problem with village government officials in Segorotambak Village is the lack of knowledge and skills of village officials regarding the management and utilization of village information systems. This program aims to increase the capacity of village officials in managing village information systems and to encourage the creation of orderly administration of the Segorotambak Village government, Sedati District, Sidoarjo Regency. The implementation methods include (a) training in the application of village information systems 3.10 in administering village apparatus administration and (b) training in the management and utilization of village information systems on a continuous basis and assistance for its sustainability. The results of the service show that (a) there is an increase in the knowledge of the village apparatus by 63% and (b) an increase in knowledge and skills in the management and use of the village information system (SID) by 62%.